Efficient Consecutive Synthesis of Fluorinated Isoflavone Analogs, X-Ray Structures, Hirshfeld Analysis, and Anticancer Activity Assessment - Mohammed Salah Ayoup; Malak Daqa; Yousef Salama; Rand Hazzam; Mohammed B. Hawsawi; Saied M. Soliman; Nawaf Al-Maharik (Molecules)
The synthesis of 7-O-carboxymethyl-4′-fluoroisoflavone 4 and 7-O-carboxymethyl-4′-fluoro-2-trifluormethylisoflavone 7 involved the cyclization of 2,4-dihydroxy-4′-fluorodeoxybenzoin 1, followed by 7-O-alkylation with methyl bromoacetate and subsequent acid-catalyzed hydrolysis. The structures of the novel compounds were validated using a range of techniques, including XRD crystallography (1H, 19F, 13C)-NMR, and IR. Only interhalogen contacts were detected in 5, while they were completely lacking in 2 and 4, owing to the presence of crystalline ethanol in the crystal structure. The %F…F in 5 was 12.2% based on Hirshfeld calculations. The aromatic π-π stacking interactions were important only in 2 and 4 but not observed in 5. Isoflavones 4, 5, and 7 displayed anticancer activity against MCF-7 cancer cells, with IC50 values of 13.66, 15.43, and 11.73 µM, respectively.